An empirical study on electronic commerce diffusion in the Malaysian shipping industry - Ang, Chooi Leng; Mat Tahar, Razman; Murat, Rusdi (City University of Hong Kong, 2003)
Electronic commerce (E-commerce) refers to business transactions conducted over computer networks, both public and private; it is abaut electronic interactions among business, governments and consumers for the purpose of information retrieval,trading, procurement, purchasing and delivery of digitalized goods and services [1].At industry level,the development of Electronic Data Interchange (EDI) has become central to the concept of E-commerce. It is an important foundation block for the implementation of E-business. To harness the capability of EDI, Port Klang was facilitation programme. The government hopes that EDI application will bring abaut greater efficiency and productivity and also be able to respond to the needs and changing requirements of trade if a port is to become a major port of call for shipping lines the world over. A decade has passed since the introduction of EDI to the shipping industry in the Port Klang might be high in term of volume. However its use was still very low and limited in terms of diversity, breadth and depth. There was hardly any transaction between other business partners except the Customs Department. Investigation on the feasibility factors revealed that initial investments, requirements of trading partners and software related issues related issues were the major problems faced by these companies.